in vitro Studies on Transdermal Absorption of Extract from Daphnes Giraldii Cortex - Ma, L.; Qu, X.C.; Han, F.; Cheng, Y.J.; Yang, C.H.; Wei, Z.P. (Asian Journal of Chemistry, 2014)
The percutaneous permeability of three major components (daphnin, daphnetin-8-O-b-D-glucoside, daphnetin) in the extract from daphnes giraldii cortex (the dried stem bark and root bark of daphne giraldii, daphne retusa and daphne tangutica) simultaneously are investigated and established the foundation for the development of transdermal delivery system of babu plaster of daphnes giraldii cortex extract. The franz diffusion cell method and razor processed excised rabbit skin were used to evaluate the transdermal absorption characteristics of daphnes giraldii cortex extract. The effects of enhancer dosage and drug loading on the percutaneous permeability were studied. The penetration rate constant (Js) was 14.9276 μg/(cm2 h) under the optimum condition. Fitting results showed that the penetration curve was related to zero level kinetic equation. This study has built the in vitro percutaneous analysis method for the active components in the extract from daphnes giraldii cortex, daphnes giraldii cortex extract has the good percutaneous permeability which suggests that it is suitable for the transdermal delivery system in the treatment of rheumatic diseases.